Aspek Legal dan Ekonomis dari Perikatan Jual Beli dalam Penyelesaian Hutang - Niswatin Khoiriyah; Bambang Arwanto (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
This research discusses the legal and economic aspects related to Sales and Purchase Agreements in the context of debt settlement. The main focus is the legal analysis of Sales and Purchase Agreements which is based on Debt-Receivable or Money Lending and Borrowing Agreements, as well as its impact on legal certainty and protection for the parties involved. This research also investigates the provisions of Articles 1457 and 1458 of the Civil Code regarding the validity of sale and purchase transactions, as well as the process of transferring land rights through a Deed of Sale and Purchase carried out by the Land Deed Official. The study results show that PPJB is often used as debt collateral, although this practice is not legally valid because Sales and Purchase Agreements and Debt-Receivable Agreements have different concepts and principles. The use of Sales and Purchase Agreements as debt collateral is considered problematic because it violates Article 1320 of the Civil Code which regulates the conditions for the validity of an agreement. This research emphasizes the importance of understanding the differences between sales and purchase agreements and accounts payable to ensure legal clarity and adequate protection for all parties involved in the agreement.